Wasiat Wajibah sebagai Hilah dalam Hukum Waris Islam - Muhammad Afif Al Haq; Lilik Andaryuni (Bulletin of Community Engagement, 2024)
Wasiat Islam is an action that is recommended to gain the approval of Allah SWT and hope for His reward. And this will is voluntary from the person who owns the assets to another party which is executed after death. In the last few decades a new law emerged called mandatory will. This obligatory will is a will intended for heirs or relatives who do not receive a share of the inheritance of the person who died, due to a sharia obstacle. This law is one of the results of Islamic law reform which first appeared in Egypt as Inheritance Law legislation in 1946 to overcome the view that male grandchildren inherit mahjub. However, in Indonesia the mandatory will in the compilation of Islamic law (KHI) has changed its function to be intended for adopted children. Basically, according to Islamic inheritance law, adopted children do not receive a share of the inheritance. The purpose of this research is to discuss the regulations on mandatory wills and understand the basics of the application of this law from the perspective of Islamic law and whether it conflicts with Islamic inheritance law, or that this mandatory will is a hilah or a deviation from Islamic law.